Harnessing Digital Skills and AI: Driving Employee Performance in the Digital Era - Handayani, Asih; Widajanti, Erni; Putri, Aisya (Universitas Brawijaya, Indonesia, 2026)
The rapid digital transformation in the banking sector presents critical challenges for rural banks (BPR), which lack the resources for structured adaptation. This issue creates an urgent need to understand the human-centered mechanisms and digital competencies interacting with technology that determine successful performance outcomes in this new era. This study aims to analyze the influence of digital skills and AI utilization on BPR employee performance, with digital competence and innovation as mediating variables. This study employed a quantitative explanatory survey method among BPR employees. Data were collected from 250 respondents selected through purposive sampling, using a structured questionnaire with a five-point Likert scale. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3 software to test the hypotheses. The study findings prove that all nine hypotheses are accepted. Digital Skills (X1) and Artificial Intelligence (X2) have a positive and significant effect on Digital Competence (Z1), Innovation (Z2), and Employee Performance (Y). AI is the strongest direct driver of performance, accompanied by Digital Competence. Digital Competence and Innovation serve as critical mediators for performance improvement investments. This study presents an integrated empirical model for Indonesian rural banks. The main practical implication is the need to prioritize the development of human resource capabilities in technology procurement by implementing tiered training to build structured digital competencies, targeted integration of AI into core processes supported by training, and building an organizational culture that encourages technology-based innovation.